Effect of the COVID-19 Pandemic on Eating Habits and Food Purchasing Behaviors of University Students - YILMAZ, Hacı Ömer; Aslan, Ramazan; Unal, Cihan (UI Scholars Hub, 2020)
COVID-19 disease, which spread rapidly all over the world after the first case was detected, became the primary agenda of the countries. Radical measures have been taken by governments to prevent the spread of the disease. Precautions and warnings to prevent disease caused some changes on daily life activities of people. University students who have to stop education are among the groups most affected by this disease sociologically, psychologically and physiologically. The aim of this study was planned and conducted to determine the effect of COVID-19 on university students' eating habits and food purchasing behavior. The study was completed with 866 university students education and training at the faculty of health sciences. Research data was obtained by online questionnaire. This questionnaire has been prepared with the information obtained as a result of the literature review and the opinions of experts by researchers. The questionnaire includes questions about eating habits and food purchasing behaviors. A result of the study, COVID-19 disease caused significant changes in the eating habits and food purchasing behaviors of university students. In general, it was found that the participants increased their consumption compared to before COVID-19, they paid more attention to hygiene while food purchasing.